(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
As safety at work has become a number one priority in every industry, it is no wonder that new technology and ideas are being tested to improve safety in a variety of workplaces, including, surface and underground mining, construction sites, power plants, factories, etc. Sensor technologies embedded in a personal protective equipment (PPE), can be employed to monitor workers’ health, exposure to harmful elements, their proximity to danger zones, etc. This technology connected with smartphone and smartwatch can also heighten workers’ awareness by collecting data on the work place itself, detecting environmental and health hazards conditions. In this paper we will present a prototype system that can be employed in underground mining which uses sensors attached to regular PPE clothing, including hard hats and safety glasses which are connected with smartphone and smartwatch via energy-efficient Bluetooth sensors, to provide real-time safety situation awareness and predict health and safety incidents before they occur.